Side Effects of Chloroquine and Primaquine and Symptom Reduction in Malaria Endemic Area (Mâncio Lima, Acre, Brazil) - Braga, Cássio Braga e; Martins, Antonio Camargo; Cayotopa, Athaid David Escalante; Klein, Wagner Werner; Schlosser, Andreus Roberto; Silva, Aline Ferreira da; Souza, Mardelson Nery de; Andrade, Breno Wilson Benevides; Filgueira-Júnior, José Alcântara; Pinto, Wagner de Jesus; da Silva-Nunes, Mônica (Interdisciplinary Perspectives on Infectious Diseases, 2015)
Side effects of antimalarial drug can overlap with malaria symptoms. We evaluated 50 patients with vivax malaria in Mâncio Lima, Acre, treated with chloroquine and primaquine. Patients were evaluated for the presence of 21 symptoms before and after treatment and for reported side effects of these drugs after treatment was started. The most frequent symptoms before medication were headache, fever, chills, sweating, arthralgia, back pain, and weakness, which were present in between 40% and 76% of respondents. The treatment reduced the occurrence of these symptoms and reduced the lack of appetite, but gastrointestinal symptoms and choluria increased in frequency. There were no reports of pale stools before medication, but 12% reported the occurrence of this symptom after treatment started. Other symptoms such as blurred vision (54%), pruritus (22%), paresthesia (6%), insomnia (46%), and “stings” into the skin (22%) were reported after chloroquine was taken. The antimalarial drugs used to treat P. vivax malaria reduce much of the systemic and algic symptoms but cause mainly gastrointestinal side effects that may lead to lack of adherence to drug treatment. It is important to guide the patient for the appearance and the transience of such side effects in order to avoid abandoning treatment.